An Analysis of Language Styles Uttered by Main Character in “Teman Tapi Menikah” Movie - Riani Juni Putri; Dohra Fitrisia; Arifin Syamaun (Universitas Syiah Kuala, 2021)
This study investigated the language styles uttered by main character in Teman Tapi Menikah movie and factors that influenced his language styles. This study belongs to descriptive qualitative research and used content analysis method to analyzed main character’s utterances. Of the 5 (five) types of language styles based on Joos’s (1976) theory (frozen, formal, consultative, casual, and intimate style), all of them were found in the object of the study. Moreover, there are 4 (four) factors that influenced main character’s language styles namely setting, function, topic, and participant.The type of language style that was mostly used by main character was casual style which mostly influenced by participant factor.The findings showed that Dito used casual style frequently because most of the conversation occured in the movie was between Dito which is the main character of the movie and his bestfriend Uca which is presented in a relaxed and casual situation. Finally, the writer suggests the next researchers to investigate further study of language style in the real community and to explore the newest theories of language styles to gain more understanding for the further research about language style.